A ESCRAVIDÃO NA PROVÍNCIA DO PARANÁ: FUGAS DE ESCRAVIZADOS PUBLICADAS NO PERIÓDICO DEZENOVE DE DEZEMBRO (1854-1888) - Mehret Filho, Leo Marcos (2021)
Based on the slave escape ads announcements published in the periodical Dezenove de Dezembro, between the years of 1854 and 1888, in Paraná, the objective of this research has been to investigate the motivation of these people have runaway, according to the report on the pages of the respective periodical. We understand, in advance, that what was reported was constructed through the eyes of the other in relation to the fugitives: if, at a certain moment, the enslaved tried to break with the situation of slavery, by means of the escape, as one of their tactics, the masters wished to recover what the law defined as their property. In this sense, newspapers became strategic tools to publicize the escapes by signaling the characteristics of the fugitives, in order to capture them. Among many issues, the announcements allowed us to think about the motivations that led them to escape, considering situations that potentiated their decisions, such as the interprovincial trafficking and the geographical displacement resulted from them and from sales, unwanted by the slaved men and women, but practiced nonethless by their masters, the family, physical and symbolic violence. We also sought to examine the paths and opportunities of the fleeing enslaved, seeking to detect possibilities of success, as they traveled through the province of Paraná, in search of freedom. With the support of a historiography, that focused on the theme of slavery, specifically in relation to the escapes, we investigated how the periodical Dezenove de Dezembro published certain narratives of the escapes of the enslaved, but, more than that, we aim to address the expectations that the actors of these actions might have had on their daily lives in slavery.